Dos números complexos aos quatérnions: desenvolvimento algébrico, interpretação geométrica e aplicações - Santos, Marcos André dos (2013)
This work was developed after observing the difﬁculties and unmotivated of the high school students to learning complex numbers. The development consisted in create a timeline in the study of complex numbers since Cardano at Sir Hamilton, expecting to contribute to understanding of this subject, associating algebraic properties and geometric interpretation, seeing to improve the understanding of the use of complex numbers to solve problems. Also, the history of imaginary unit i introduction and representation two-dimensional (2D) complex numbers a+bi, extending this for four-dimensions(4D) quaternions numbers a+bi+cj+dk, and its less usual forms like matrix form, vector form, including the procedure used in the rotation, showing your importance as motivation in the teaching of geometry, in physics and graphic computation.